Mitigating Financial Statement Fraud through Fraud Heptagon, Digital Forensics, and Risk Management: ‎Evidence from Indonesia’s StateOwned Enterprises - Ghozali, Imam; Achmad, Tarmizi; Hersugondo; Pamungkas, Imang Dapit (International Journal of Accounting and Economics Studies, 2025)
Financial statement fraud poses a critical threat to organizational integrity and stakeholder trust worldwide, particularly in state-owned enterprises (SOEs) where public accountability is paramount. This study investigates how the Fraud Heptagon framework, digital forensics, and ‎risk management practices mitigate financial statement fraud, providing insights relevant for both national and international contexts. A ‎mixed-methods approach was adopted, combining quantitative analysis of 116 firm-year observations from 68 SOEs listed on the Indonesia ‎Stock Exchange during 2020–2024 with qualitative data from semi-structured interviews with auditors, risk officers, and forensic specialists. ‎The quantitative results reveal that the integrated Fraud Heptagon dimensions, including greed, opportunity, pressure, rationalization, capability, arrogance, and collusion, significantly drive financial statement fraud, while digital forensic tools and risk management mechanisms ‎effectively moderate these effects. Qualitative findings emphasize that systemic pressures, operational demands, and institutional weaknesses ‎foster fraudulent behaviors, whereas technological and risk-based interventions enhance detection, transparency, and organizational accountability. This study underscores that financial statement fraud is primarily a systemic phenomenon rather than an outcome of isolated individual misconduct, highlighting the necessity of integrating behavioral frameworks with technological enforcement and structured governance. ‎By applying the Fraud Heptagon alongside digital forensics and risk management, organizations can implement a comprehensive fraud prevention strategy. The results offer valuable implications for policymakers, regulators, and corporate governance bodies globally, emphasizing-‎ing the importance of robust fraud detection, prevention mechanisms, and transparency to safeguard financial reporting integrity in public ‎and private sectors‎.